Synthesis of p-N-substituted Tertiary Aminophenyl-4'-substituted Phenyl Ketone and Their Derivates as Potent Antifungal Agents - Afsah, S.A.; Nayyer, S.A.; Ahmad, J. (Asian Journal of Chemistry, 2010)
Several new p-N-substituted tertiary aminostyryl-4´-substituted phenyl ketone and some of their derivatives have been prepared. The structures have been supported by analysis and spectral data. Some of the compounds have been screened for their antifungal activity against F. oxysporum, P. italicum. H. sativum and C. lunata.